The effect of preoperative structural changes and postoperative perfusion on the functional restoration of the retina in the surgical treatment of full-thickness macular holes - T.A. Doktorova; A.A. Suetov; E.V. Boiko (Офтальмохирургия)
Purpose. To evaluate effect of preoperative local structural retinal changes and capillary perfusion in idiopathic full-thickness macular holes (FTMH) on the recovery of functional activity of the retina after surgical treatment. Materials and methods. We used optical coherence tomography (OCT) and OCT-angiography (OCT-A), microperimetry, multifocal electroretinography. In 25 eyes with FTMH the density of capillaries in the superficial and deep capillary plexus (SCP and DCP), retinal sensitivity (RS), amplitude and implicit time of P1 were studied at 13 points located at different distances from the fixation point were evaluated. Data were analyzed in the projection of the hole, intraretinal cystic changes (ICC), neuroepithelial detachment (NED) and intact retina before surgical treatment, 7 days, and 3 months after. Results.In the area of hole, ICC, and NED, in comparison with intact areas of the retina, a significant decrease in RS, an increase in implicit time and a decrease in amplitude of P1, and a decrease in capillary density in the SCP and DCP were revealed. Functional restoration of the retina with an increase in its perfusion was noted 3 months after the surgery. The correlation was found between postoperative changes in RS and changes in capillary density in the SCP in the projection of NED (R=0.32, p=0.001) and ICC (R=0.19, p=0.001), as well as in the DCP in the projection of NED and ICC (R=0.31, p=0.001). The change in the amplitude P1 in the postoperative period significantly correlated with the change in perfusion in the SCP in the projection of the NED (R=0.38, p=0.001) and the hole area (R=0.31, p=0.001), as well as in the DCP in the projection of the ICC (R=0.31, p=0.01) and in the area of NED (R=0.28, p=0.001). Conclusion. Thus, when using a multimodal topographically oriented approach, a relationship was found in the postoperative period of changes in functional parameters at various points in the macular area with changes in local perfusion at the level of both SCP and DCP, while the relationship is most significant in the projection of NED along the tear edge and in the areas of ICC.